Chronic periodontitis chief complaints: gender and age distribution; their correlation with plaque index and probing pocket depth (Mustansiria Dental Journal, 2018)
To determine the most common chief complaints of chronic periodontitis patientsto assess the public awareness about this disease symptoms, their distribution amongmales & females and their correlation with age and some of periodontal parameters(PLI & PPD).Chief complaints of 1115 (641 males & 474 females) chronic periodontitispatients attending the College of Dentistry/ University of Baghdad seeking treatment.The age range was from 23 to 67 years; the mean age was 46.1. The patients dividedaccording to age groups & according to gender.The majority of patients expressing symptoms of chronic periodontitis weremainly between 40 and 60 years old. A highly significant difference between malesand females in referral and bleeding (P value= 0.001), a significant difference inmobility, altered gingival appearance, and pain (P value= 0.004, 0.022, and 0.002respectively); the other chief complaints (pathologic tooth migration and malodor)showed no significant differences between the two groups (males & females)(Pvalue= 0.909, and 0.872). The highest complaint was bleeding (about 31%) followedby referred patients (19.6%), while the malodor was the least reported chiefcomplaints (5.5%). An obvious correlation between chief complaints and age withPPD and PLI for all chief complaints groups.This study showed that there is an ignorance of the nature of periodontal diseaseson a community level which calls for more education programs to be carried out bydental team members concerning the proper oral hygiene measures instruction andmotivation to reverse or at least minimize the effect of periodontal disease(s).